2016
DOI: 10.1038/srep33589
|View full text |Cite
|
Sign up to set email alerts
|

Transient exposure to calcium ionophore enables in vitro fertilization in sterile mouse models

Abstract: Mammalian sperm acquire fertilizing capacity in the female tract in a process called capacitation. At the molecular level, capacitation requires protein kinase A activation, changes in membrane potential and an increase in intracellular calcium. Inhibition of these pathways results in loss of fertilizing ability in vivo and in vitro. We demonstrated that transient incubation of mouse sperm with Ca2+ ionophore accelerated capacitation and rescued fertilizing capacity in sperm with inactivated PKA function. We n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 46 publications
1
50
0
Order By: Relevance
“…Moreover, a short (10 min) exposure to A23187 can rescue defects in hyperactivated motility and the fertilizing capability of CatSper1 -null sperm in vitro (Navarrete et al, 2016). We tested the relation of calcium transients to hyperactivated motility in CatSperz -het and null sperm.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a short (10 min) exposure to A23187 can rescue defects in hyperactivated motility and the fertilizing capability of CatSper1 -null sperm in vitro (Navarrete et al, 2016). We tested the relation of calcium transients to hyperactivated motility in CatSperz -het and null sperm.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas P2X2 KO mice are fertile, lack of CatSper results in complete sterility (14,41,42). Recently, we have shown that the lack of hyperactivation and infertility phenotypes can be overcome elevating [Ca 2ϩ ] i pharmacologically by exposing CatSper KO sperm to A23187 for a short period of time (43). Although the role of CatSper is well established in sperm function, how this channel complex is regulated is still not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, calaxin is indispensable to the Ca 2+ ‐dependent antisymmetrisation of flagellar bending and directly decelerates the sliding of microtubules in ascidian spermatozoa. Meanwhile, a treatment with A23187 rescues the ability to fertilize oocytes (including the capacity to undergo hyperactivation) in spermatozoa from infertile CatSper1 ‐, Adcy10 ‐, or Ksper ( Slo3 )‐KO mice, but does not recover it in spermatozoa from infertile Pmaca (Ca 2+ efflux pump on the plasma membrane)‐KO mice, suggesting importance of a transient increase in cytoplasmic Ca 2+ in the expression of fertilizing ability including the ability to undergo hyperactivation . Thus, it may be also necessary to focus on roles of the clearance of cytoplasmic Ca 2+ in the occurrence of hyperactivation.…”
Section: Regulatory Mechanisms For Flagellar Hyperactivationmentioning
confidence: 99%
“…Pmaca (Ca 2+ efflux pump on the plasma membrane)-KO mice, suggesting importance of a transient increase in cytoplasmic Ca 2+ in the expression of fertilizing ability including the ability to undergo hyperactivation. 81 Thus, it may be also necessary to focus on roles of the clearance of cytoplasmic Ca 2+ in the occurrence of hyperactivation. Technology Center for Agriculture, Forestry and Fisheries), and students and staffs of our laboratory for their significant contribution to our research projects.…”
Section: Ko Mice But Does Not Recover It In Spermatozoa From Infertilementioning
confidence: 99%